A felicidade na Ética a Nicômaco de Aristóteles: fim dominante ou inclusivo? - Gomes, André Luiz [UNESP] (2015)
In this dissertation, we had intended to present the problem related to definition of eudaimonia in the Nicomachean Ethics (EN), namely: the two perspectives on the Aristotelian happiness. Aristotle says in that work, the ethical knowledge, seeks to know the good for man. This good is identified by the philosopher with happiness, but we must not understand happiness as simple psychological state, but as consisting of a soul activity according to virtue. Addition, a serious problem arises related to the concept of virtue. Interpretation entitled dominant, which is based mainly on EN X, illustrates happiness as ownership of intellectual contemplation of virtue (sophia), or life dedicated to philosophical wisdom as the most excellent and able to make a happy life. In contrast, if we consider EN I, to EN IX, we can also find the inclusive perspective, which in its mitigated version shows another central virtue, virtue proper, which arises from an enhancement of natural virtue (aretê), when it is united with prudence (phrónesis). However, just the possession of virtue itself, does not guarantee happiness, in this version, the happy man must also have: the external goods, goods of the body and the goods of the soul. It is the possession of these three classes of goods, each consisting of assets that guarantee self-sufficiency (autarkeia) citizen, that enable the happy life be the case.